Project Management: Defining Competences for Translator Training - Plaza-Lara, Cristina (Peter Lang, 2018)
Existing research on translation project management is rather scarce, despite the fact that this professional profile has become a common career option for Translation and Interpreting graduates. However, the lack of definition regarding the competences of translation project managers makes it difficult for trainers to incorporate these contents into their classrooms. In this paper, an approach to the definition of the competences of translation project managers will be presented. To this end, the theoretical framework of translation and project management competences will be reviewed, and a proposal for a model of competences will be offered. Subsequently, taking this theoretical framework as a starting point, translation curricula in Spanish universities will be analysed in order to operationalise, from an academic point of view, the different components of the model of competences suggested. Finally, different proposals for integrating project management as a cross-curricular competence will be addressed, not only through specific modules but also through the incorporation of these contents in the translation process.
Política de acceso abierto del editor: http://biblioteca.cchs.csic.es/registro_buscareditoriales.php?id=699
Keywords: Traductores - Formación profesional; Gestión de proyectos; Formación de traductores; Competencias profesionales; Currículos en traducción; Competencias transversales